Evaluation of Service Charge Determination as a Veritable Tool for Managing Multi-Tenanted Properties in Edo State - D., Adekunle (International Journal of Real Estate, 2025)
Over the years, service charges have given rise to several disputes and issues for landlords and tenants, including selecting the contractor to perform the services. Disagreements and legal action may result from failure to pay service charges when they are due. This study uses the Edo State as a case study to investigate how service charges are administered in commercial buildings. The study looked at the services that go into administering service charges, how they are used, and the difficulties in doing so. The study utilized a quantitative methodology in which thirty questionnaires were sent to the building’s residents in the designated study area. The sampling strategy employed was purposeful sampling. Descriptive statistics were used to assess the received data. The study’s conclusions show that although the retail complex used the space volume technique of allocating service charges, the tenants prefer the fixed percentage method. The results also indicate that the main obstacles to service fee management were an unfavorable economy and some tenants’ payment defaults. It’s interesting to note that, aside from elevator and air conditioning system servicing, all services and amenities that make up a service charge were provided to renters in the case study, according to the analysis. The report suggests holding scheduled meetings to settle disputes between managers and tenants. To improve user service at Edo State, service providers should increase service offerings and hire professionals to maintain the facilities properly.